Influence of Socio Economic Variables on Level of Adoption of Prawn/Fish Pickle Making Technology - K., Ponnusamy; M., Jayanthi; M., Kumaran; N., Thenmathi (Fishery Technology, 2025)
The study attempts to explore the level of adoption of prawn/fish pickle making technology by coastal fisherwomen and the influence of socio economic variables on the adoption. Level of education, social participation, extension agency contact, mass media exposure, risk orientation and economic motivation were found to be the factors influencing awareness, knowledge level and adoption of the technology.